Technical and technological modernization of Azerbaijan economy: solutions - Gulshen Yuzbashieva; Israfil Yuzbashiev (Challenges and Issues of Modern Science)
The technical and technological modernization of the Azerbaijan economy at the current stage of development does not yet meet the requirements of long-term economic growth and development. Today, a lot of work is being done to overcome the technical and technological gap with developed countries, despite some local achievements, which requires a large-scale one. The lack of modern market relations, the low level of competition is one of the causes of technical and technological problems, which reveals the need to find our own way of effective modernization of the economy.